2015
DOI: 10.1016/j.ijforecast.2014.08.015
|View full text |Cite
|
Sign up to set email alerts
|

EuroMInd-C: A disaggregate monthly indicator of economic activity for the Euro area and member countries

Abstract: The paper deals with the estimation of monthly indicators of economic activity for the Euro area and its largest member countries that possess the following attributes: relevance, representativeness and timeliness. Relevance is determined by comparing our monthly indicators to the gross domestic product at chained volumes, as the most important measure of the level of economic activity. Representativeness is achieved by considering a very large number of (timely) time series of monthly indicators relating to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…In addition, our models are instrumental to unveil the current course of fiscal policy in real-time, which complement a different literature, focused on forecasting, that usually treats government expenses as exogenous in macro scenarios because they are considered erratic and difficult to forecast (see e.g. Grassi et al, 2014). 6 A recent literature in the field of short-term forecasting that has shown that the use of high-frequency fiscal data may improve budget forecasting and monitoring.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…In addition, our models are instrumental to unveil the current course of fiscal policy in real-time, which complement a different literature, focused on forecasting, that usually treats government expenses as exogenous in macro scenarios because they are considered erratic and difficult to forecast (see e.g. Grassi et al, 2014). 6 A recent literature in the field of short-term forecasting that has shown that the use of high-frequency fiscal data may improve budget forecasting and monitoring.…”
Section: Introductionmentioning
confidence: 91%
“…Exceptions are Baffigi et al (2004), which follow a demand-side approach, Hahn and Skudelny (2008), that follow a supply-side approach, or Foroni and Marcellino (2013), who look at both sides of GDP. In those papers, nevertheless, g and the relevant supplyside counterparts tend to be forecasted by means of univariate methods, or considered to be a residual, exogenous variable difficult to model and forecast, and considered to be erratic (in this latter regard see also Grassi et al, 2014). Another set of papers consider the elaboration of optimal government forecasts with a view to orient the ex-ante design of policies (see, for early contributions, Johansen, 1972, Granger, 1973, Johansen and Hersoug, 1975.…”
Section: Related Literaturementioning
confidence: 99%
“…Koop and Korobilis (2014) also consider an SSM with time-varying parameters. Furthermore, dt and ct could be dierent from zero when there are deterministic components; see, for example, Grassi, Proietti, Frale, Marcellino and Mazzi (2015) and Jungbacker and Koopman (2015), among many others. Most of the procedures described in this paper can be extended to these cases.…”
Section: Kalman Lter and Smoothing Algorithmsmentioning
confidence: 99%
“…For factor extraction, we need to apply the Kalman lter to the low-dimensional series, Y L t ; see Grassi et al (2015) for an empirical application.…”
Section: Kalman Lter and Smoothing Algorithmsmentioning
confidence: 99%
“…Most recently, the literature has proposed further methodological developments mainly due to the initiative by Eurostat (see, among others, Frale, Marcellino, Mazzi, & Proietti, , ; Grassi, Proietti, Frale, Marcellino, & Mazzi, ; Moauro, ). At the same time, ISTAT favored a relatively more pragmatic approach.…”
Section: Introductionmentioning
confidence: 99%